The Preference for English in Digital Media among Indonesian Millennials - Harjanto, Ignatius (Widya Mandala Catholic University Surabaya, 2021)
The use of English among Indonesian millennials has been more widespread especially because of exposure to English has been so massive to secondary school in urban areas. There has been a concern that the increasing use of English might diminish their Indonesian language use and cultural identity.Â This study aims to investigate the roles of English on satellite TV programs and social media posts for Indonesian millennials, their language preference, and the consequences of language preference on their national identity. A concurrent embedded mixed methods design collecting quantitative and qualitative data was carried out through short essays and closed-questionnaires. Both questions of essay writing and closed-questionnaires were sent to students of private high schools in two big cities (Jakarta and Surabaya), aged 18 to 20 years old online. The questionnaire items were in multiple-choice and the short paragraph essay explained the importance of TV programs and social media posts for learning English. After being scrutinized, 989 respondentsâ€™ essay responses were analysed. The findings showed that TV programs and social media posts were claimed to have important roles of English learning resources. Although they practiced English through social media, they felt that they still kept themselves as Indonesians when using English on social media